(untitled) (Linguist, 2025)
The illocutionary act of an utterance conducts effect on the receiver in different ways among which “securing the uptake” is one of the very important. Illocutionary acts are bound up with the effect through securing the uptake. Such an illocutionary effect is distinct from the perlocutionary effect. The context of the utterance, the shared background between the speakers and the listeners as well as the social conventions shared between the speaker and the receiver are the main basics for the listener to go beyond the literal meaning of the utterances and reach the embedded meaning encoded by the speaker through language.